Damage costs of climate change through intensification of tropical cyclone activities: An application of fund - Daiju Narita; Richard S. J. Tol; David Anthoff (The Economic and Social Research Institute (ESRI), 2008)
Climate change may intensify tropical cyclone activities and amplify their negative economic effects. We simulate the direct economic impact of tropical cyclones enhanced by climate change with the integrated assessment model FUND 3.4. The results show that in the base case, the direct economic damage of tropical cyclones ascribed to the effect of climate change amounts to 19 billion globally (almost the same level as the baseline (current) global damage of tropical cyclones) in the year 2100, while the ratio to world GDP is 0.006%. The US and China account for much of the absolute damage, whereas small island states incur the largest damage if evaluated as the share to GDP. The results also show that they are sensitive to the choice of baseline and of the wind-speed elasticity of storm damage.
Keywords: 330; climate change; tropical storms; economic impact; Klimaveränderung; Naturkatastrophe; Sturm; Katastrophenschaden; Makroökonomischer Einfluss; Schätzung; Welt